Peranan Komunikasi Interpersonal Antara Guru Bimbingan Konseling (BK) dengan Siswa dalam Menangani Kenakalan Siswa (Studi Kasus di SMP Kristen 2 Salatiga) - Timothius, Johan Chris (Master of Communication Science Program, Faculty of Social and Political Science, Diponego, 2016)
AbstractCommunication is one of the most parts in human life. There are several types of communication: interpersonal communication, intrapersonal communication, and mass communication. This study focused on interpersonal communication in education between the teacher and the students. The aim of this study was to know the function of interpersonal communication to solve students’ matter at school. The study conducted in SMP Kristen 2 Salatiga, because the school has had face the problems.The qualitative method was used. Interview and observation were used to collect the data the interview and observation are done with four persons as key respondent: three students and one teacher as counselor. Then, triangulation and content analysis were used to know the respondents’ pattern.The data analysis showed that interpersonal communication gave contribution to solve the students’ matter. The teacher himself should be active by using client center and exchange theory to solve the students’ problem. Furthermore, if there are some matters between teacher and students or students to students, interpersonal communication is the effective way to solve the problems.Keywords: interpersonal communication, education, students’ problem.